COMPOSICIÓN Y ABUNDANCIA DE LA ARTROPODOFAUNA TERRESTRE EN LA PENÍNSULA FILDES - Trillo, Mariana C.; Stanley, Estefanía; Rodríguez, Valeria; Laborda, Álvaro; Castro, Manuel (Boletín de la Sociedad Zoológica del Uruguay, 2018)
The first complete survey of the terrestrial and aerial artopodofauna present in the Artigas Scientific Base and its surroundings was carried out. The samplings were performed during February 2015 within the project “Composición y estructura de la Artrópodo-fauna en áreas cercanas a la Base Científica Antártica Artigas” founded by Instituto Antártico Uruguayo (IAU). We found four arthropod orders, in which Coleoptera is the first report of the order for the South Shetland Islands.